Cluster analysis of marketing communication - A. V. Balabanova; G. T. Zhuravlev (Путеводитель предпринимателя, 2020)
The article discusses the study of motives of consumer behavior on the market of information services; methods of collection of marketing information and its analysis; the role and methods of cluster analysis.